Nontraumatic Fat Embolism Found Following Maternal Death after Cesarean Delivery - Tabitha Schrufer-Poland; Paul Singh; Cristiano Jodicke; Sara Reynolds; Dev Maulik (Thieme Medical Publishers, Inc., 2015)
Abstract Introduction Fat embolism is a rare form of nonthrombotic embolization. Limited literature exists regarding the diagnosis of fat embolism during the perinatal period. We present the first case of maternal death that resulted from nontraumatic fat embolization following Cesarean delivery. Case Description A 29-year-old gravida 1 with a complex medical and surgical history underwent a primary Cesarean delivery at term. On postoperative day 2 the patient was found to be unresponsive. Despite resuscitative efforts, the patient succumbed. Autopsy findings were remarkable for diffuse pulmonary fat emboli. Furthermore, there was no histological evidence of either amniotic fluid embolism or thromboembolism. The primary cause of death was attributed to nontraumatic fat embolization. Discussion Multiple risk factors may have contributed to the development of nontraumatic fat embolization in our patient. Obstetricians should maintain a high level of suspicion for nontraumatic fat embolization in cases of maternal respiratory decompression and sudden maternal mortality.